Adsorption of Silver Nanoparticles on Glass Beads Surface - Izabela Polowczyk; Tomasz Koźlecki; Anna Bastrzyk (Adsorption Science & Technology)
Colloidal silver is widely used owing to its specific properties, which enable it to be applied in various fields. In this work, adsorption of commercially available silver nanoparticles (AgNPs; NanoSilver PVP 1000) on glass beads was investigated. The glass microspheres (70–110 μm) were used as model particles. The adsorption of AgNPs on the glass beads surface was investigated in terms of adsorbent dosage. The adsorption isotherm was determined with the adsorbent dosage of 100 g/l and the AgNPs in range 100–1000 mg/l. It was found that adsorption isotherm data best fitted the Langmuir model. Kinetics of AgNPs adsorption onto glass beads followed a pseudo-second-order model. The interaction between glass microspheres surface and polyvinylpyrrolidone (PVP)-coated AgNPs is due to hydrogen bonding with oxygen of carbonyl groups of PVP and silanol groups on the glass surface.